Pemberdayaan Ibu Cerdas: Sosialisasi Imunisasi Polio Tetes (OPV) dan Suntik (IPV) untuk Perlindungan Optimal Anak Wilayah Kerja UPTD Puskesmas Patek - Diana Lestari; Nia Hairu Novita; Yuliana Abty (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Polio is a dangerous infectious disease that can cause permanent paralysis, but it can be effectively prevented through immunization. Optimal routine immunization coverage requires a good understanding from parents, especially mothers, as the primary decision-makers in family health. The Patek Community Health Center (Puskesmas) working area faces challenges in optimizing polio immunization coverage due to misinformation and parental concerns about side effects. This community service activity, titled